Doughnut economics : seven ways to think like a 21st-century economist - Raworth, Kate, 1970- (London : Random House, 2017)
Economics matters. Its theories are the mother tongue of public policy, the rationale for multi-billion-dollar investments, and the tools we use to tackle global poverty and manage our planetary home. Pity then or more like disaster that its fundamental ideas are centuries out of date, but still dominate decision-making for the future. Instead of criticising the past, this book takes the long view forwards, identifying seven insights to help the twenty-first-century economist bring humanity into the global sweet spot (shaped like a doughnut) that combines human prosperity with ecological sustainability. Doughnut Economics hand-picks the best emergent ideas ranging from ecological, feminist, behavioural, and institutional economics to complexity thinking, systems dynamics, and Earth-systems science to reveal the insights of eclectic economic rethinkers. It promises that the economic future will be fascinating, but wildly unlike the past, if we equip ourselves with the mindset needed to take it on.
Keywords: Economic forecasting; Economics